2012
DOI: 10.1371/journal.pone.0044550
|View full text |Cite
|
Sign up to set email alerts
|

Social Vocalizations of Big Brown Bats Vary with Behavioral Context

Abstract: Bats are among the most gregarious and vocal mammals, with some species demonstrating a diverse repertoire of syllables under a variety of behavioral contexts. Despite extensive characterization of big brown bat (Eptesicus fuscus) biosonar signals, there have been no detailed studies of adult social vocalizations. We recorded and analyzed social vocalizations and associated behaviors of captive big brown bats under four behavioral contexts: low aggression, medium aggression, high aggression, and appeasement. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
70
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(79 citation statements)
references
References 64 publications
8
70
1
Order By: Relevance
“…The recordings we made included search, approach and terminal phase calls (Griffin et al, 1960;Surlykke and Moss, 2000), which confirmed that the bats were foraging and not commuting from one site to another, corroborating a previous report of this area as a hunting field for E. fuscus (Surlykke and Moss, 2000). We did not record any calls that could be characterized as E. fuscus social calls (Gadziola et al, 2012;Wright et al, 2013Wright et al, , 2014. The AMSL of the echolocation calls recorded was 133-138 dB (RMS re.…”
Section: Discussionsupporting
confidence: 88%
“…The recordings we made included search, approach and terminal phase calls (Griffin et al, 1960;Surlykke and Moss, 2000), which confirmed that the bats were foraging and not commuting from one site to another, corroborating a previous report of this area as a hunting field for E. fuscus (Surlykke and Moss, 2000). We did not record any calls that could be characterized as E. fuscus social calls (Gadziola et al, 2012;Wright et al, 2013Wright et al, , 2014. The AMSL of the echolocation calls recorded was 133-138 dB (RMS re.…”
Section: Discussionsupporting
confidence: 88%
“…Synthetic acoustic stimuli (noise and tone bursts, 0.5 ms rise-fall time; 10 -64 ms duration) and previously recorded social vocalizations were presented at one/s. Social vocalizations consisted of 11 species-specific syllables or a combination of syllables that were previously related to aggressive (eight calls) or appeasing (three calls) behavioral contexts (Gadziola et al 2011). Duration of social vocalizations ranged from 7 to 126 ms.…”
Section: Acoustic Stimulation and Physiological Recordingmentioning
confidence: 99%
“…For example, the sinFM syllable illustrated in Fig. 8A was observed during higher levels of aggression (Gadziola et al 2011), and syllable duration varied according to the number of cycles of frequency modulation (range: 1-5 cycles; 9 -73 ms duration). When this syllable was extended by 8 ms to include a second cycle of frequency modulation (Fig.…”
Section: Contextual Features Of Amygdalar Responsesmentioning
confidence: 99%
“…The physical attributes of distress vocalizations have been intensively studied (see346161923242526272829) but, at present, comparably little is known about how distress signals are processed in the listeners’ brain, especially at the level of the auditory cortex (AC). Distress vocalizations are produced in the form of “sequences” composed of individual sound units defined as “syllables”41924253031.…”
mentioning
confidence: 99%